STRUCTURE-BORNE TRANSMISSIBILITY EVALUATION THROUGH MODELING AND ANALYSIS OF AIRCRAFT VIBRATION DAMPERS doi: 10.5028/jatm.2011.03021611 - Isabel Lima Hidalgo; Airton Nabarrete; Marcelo Santos (Journal of Aerospace Technology and Management, 2011)
In the aircraft industry a great practical relevance is given to the extensive use of vibration dampers between fuselage and interior panels. The proper representation of these isolators in computer models is of vital importance for the accurate evaluation of the vibration transmission paths for interior noise prediction. In general, simplifi ed models are not able to predict the component performance at mid and high frequencies, since they do not take into account the natural frequencies of the damper. Experimental tests are carried out to evaluate the dynamic stiffness and the identifi cation of the material properties for a damper available in the market. Different approaches for its modeling are analyzed via FEA, resulting in distinct dynamic responses as function of frequency. The dynamic behavior, when the damper natural modes are considered jointly with the high modal density of the plate that represents the fuselage, required the averaging of results in the high frequency range. At this aim, the statistical energy analysis is then used to turn the comparison between models easier by considering the averaged energy parameters. From simulations, it is possible to conclude how the damper natural modes infl uence the dynamic response of aircraft interior panels for high frequencies.